Decentralizing aid with interested parties - Gil S. Epstein; Ira N. Gang (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper analyses the decentralization of decisionmaking in aid-giving in a theoretical rent-seeking framework. In this analysis the root donor establishes a necessary criterion for potential recipients: good governance. The potential recipients compete in hierarchal contests for funds. The paper investigates whether, under certain reasonable conditions, fashionable aid procedures will lead to the development of a poverty trap.
Keywords: O10; O19; F35; O11; C23; O47; E21; E22; 330; foreign aid; governance; decentralization; rent seeking; Entwicklungshilfe; Dezentralisierung; Rent Seeking; Theorie; Politische Entscheidung; Good Governance